Development of an electronic measuring device for height and nutritional status equipped with artificial intelligence for screening stunting toddlers - Istiqomah, Nursita; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih; Mulyantoro, Donny Kristanto (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Background: Technological advancements have changed various aspects of human life, including in the world of health. One technological breakthrough that dominates attention is artificial intelligence (AI). Artificial intelligence has proven its potential to revolutionize many fields, including the health sector. One of the urgent health problems that requires innovative solutions is detecting the problem of stunting in children under five. Purpose: The study aims to develop and test a measuring device that effectively determines the body height and nutritional status in toddlers 0-5 years. Method: This study is in Research and Development (R&D); it consisted of 5 stages: stage I (literature study), stage II (product development), stage III (expert validity and phase trials), stage IV (product revision and final product), and stage V (phase II trials). Results: The electronic measuring device for height and nutritional status has been created. The result is that the tool effectively determines the height and nutritional status. The value of the ultrasonic sensor works quite well, with a maximum test error value of 0.11 and an average of 0.033, which means the calibration value of the tool's sensitivity is valid in determining body height. Conclusion: The electronic measuring device effectively determines the body's height and nutritional status.